Criminal and legal problems of fight against early and compulsory marriages in RK. (Journal of actual problems of jurisprudence, 2016)
The problem of compulsory marriages, marriages without consent of one or two partners, with application of physical or mental abuse, is especially actual today and is among the most acute social issues of the present. Early marriages, and also kidnappings of brides, or stealing for the purpose of marriage which happen against the will of girls are connected with compulsory marriages, and often interfaced to physical and sexual abuse.Compulsory marriage, early marriage is considered recently, it isn’t unreasonable, as the modern expression of slavery concerning, first of all, women, but also and men. Therefore the state and society are faced by a task to prevent early and compulsory marriage and respectively to create and improve concrete opportunities of their prevention. It demands realization of a package of measures, including, and the legislative plan.
Keywords: compulsory marriage; kidnapping; criminal liability; criminal law; criminal rule of law; criminalization